Functional Outcomes of Tension Band Wiring Using Cannulated Screws in Transverse Patellar Fracture - Ramjan Ali, Mohammad; Kumar Das, Chandan; Rahman, Abdur; Chowdhury, Avijit; Tosh Nath, Asho; Nurul Islam, Dewan (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: The most commonly used surgical intervention for treatment of patellar fractures is open reduction and internal fixation with Kirschner wire (K-wire) tension band. To overcome some disadvantages related to K-wire, a new technique has evolved replacing K-wire with cannulated screw. The aim of this study was to evaluate effectiveness and safety of open reduction and internal fixation of closed transverse patellar fractures with Tension Band Wiring (TBW) using parallel cannulated compression screws. Materials and methods: This prospective study was conducted in the Department of Orthopedic Surgery of Chittagong Medical College Hospital from January 2019 to December 2019. Twenty consecutive patients of closed transverse patellar fractures were enrolled in the study and treated with vertical skin exposure, fracture open reduction and internal fixation by anterior TBW through 4.0 mm Cannulated screws. The patients were followed post-surgery for 6 months to evaluate time required for radiographic bone union, knee joint Range of Motion (ROM) loss of fracture reduction, material failure and the overall functional result of knee using Bostman scoring. Results: The mean age of the patients was 38.91 ±12.01years and 80% were male. At final follow up 15 (75%) patients had full extension and ROM 120 degree and 5 (25%) patients had ROM 90-120 degree. The main postoperative complication was knee stiffness observed in 10% patients. Almost 95% patients had no pain and returned to their original job after 18 weeks of fixation with no significant limitations. The fractures united at a mean of 8.0±2.4 weeks (Range 6 to 10 weeks) and no case of non-union was observed. Evaluation of outcome at 24 weeks after fixation showed that 60% of the patients had excellent outcome (Bostman Score 28- 30) and 40% had good outcome (Bostman Score 20-27). Conclusion: TBW with cannulated compression screws is a safe and effective technique for the treatment of closed transverse patellar fractureswith less chance of implant failure and soft tissue irritation. Chatt Maa Shi Hosp Med Coll J; Vol.24 (1); Jan 2025; Page 41-45